The Business Strategy of the Indonesian Air Transportation Sector During the COVID-19 Pandemic - ADRIWATI, Adriwati (KnE Social Sciences, 2022)
The purpose of this study was to examine the airline industry’s business strategy during the COVID-19 pandemic. This investigation focused on PT Garuda Indonesia. A qualitative approach was used, and the research was descriptive in nature. Data were collected through in-depth interviews with key informants and Garuda Indonesia service users, such as the Senior Manager for Operations and Engineering, Garuda Indonesia ticket sales customer service officers, airport officers, PT Garuda employees, and Garuda Indonesia plane passengers. The data were analyzed using the SWOT method. According to the findings, during the COVID-19 pandemic, PT Garuda Indonesia implemented several business strategies, including providing safe and comfortable facilities for Garuda Indonesia airline passengers by implementing strict health procedures, and expanding the cargo service business through freight forwarding services. Sponsors of other companies who wanted to promote their products on Garuda planes could use the digital KIRIM AJA. It can be concluded that PT Garuda Indonesia is acutely aware of the COVID-19 pandemic’s impact on its business continuity and has been attempting to implement various strategies to survive the pandemic by first assessing the company’s strengths and weaknesses, as well as the opportunities and challenges it faces. Keywords: air transportation, COVID-19, business strategy, SWOT analysis